2023
DOI: 10.5772/intechopen.110630
|View full text |Cite
|
Sign up to set email alerts
|

Constructed Wetlands Process for Treating Sewage to Improve the Quantitative and Qualitative Management of Groundwater Resources

Abstract: Water scarcity limits access to safe water for drinking and communities face some form of water stress, which can be related to insufficient supplies or inadequate infrastructures. Climate change plays a crucial role in water stress worldwide, as rising temperatures lead to more unpredictable weather and extreme weather events. In face of this challenge, the need to seek an alternative to protect groundwater resources and to decrease the use of public water is imposed. Sewage management seems to be a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…In a constructed wetland, wastewater is first treated to remove large particles and solids before being directed into a bed of gravel or soil. The bed is then planted with a variety of wetland plants, such as cattails, reeds, and rushes, which help to absorb and filter out pollutants (Achak et al 2023). As the water flows through the bed, it comes into contact with the plants' roots and the microorganisms that live in the soil, which break down organic matter and convert nutrients like nitrogen and phosphorus into forms that are less harmful to the environment.…”
Section: Mathew J T; Inobeme A; Musah M; Azeh Y Abdullahi A; Shaba E ...mentioning
confidence: 99%
“…In a constructed wetland, wastewater is first treated to remove large particles and solids before being directed into a bed of gravel or soil. The bed is then planted with a variety of wetland plants, such as cattails, reeds, and rushes, which help to absorb and filter out pollutants (Achak et al 2023). As the water flows through the bed, it comes into contact with the plants' roots and the microorganisms that live in the soil, which break down organic matter and convert nutrients like nitrogen and phosphorus into forms that are less harmful to the environment.…”
Section: Mathew J T; Inobeme A; Musah M; Azeh Y Abdullahi A; Shaba E ...mentioning
confidence: 99%
“…The author observed that hyacinth plants were able to increase the BOD/COD ratio of industrial wastewater from 0.05-0.11 to 0.30-0.52, with simultaneous high-significant COD removals. However, for better efficiency of constructed wetlands, pretreatment of wastewater is necessary to remove various contaminants (e.g., TSS) and thus reduce the potential risk of system clogging [42]. The precipitation of nondegradable pollutants on the substrate surface is also one of the reasons for clogging [43].…”
Section: Industrial Wastewater Treatment Strategiesmentioning
confidence: 99%